Investigation of the state of investment support of sustainable development of the leading branches of the national economy of Ukraine - Latysheva, O.; Chemerys, Ye. (Економічний вісник Донбасу, 2018)
The article is devoted to the analysis of the state and specifics of the development of the leading branches of the national economy of Ukraine. The changes of the position of Ukraine in the world according to the main indicators of international ratings are investigated, namely: the index of investment attractiveness, the index of global competitiveness, the index of economic freedom, the index of the level of ease of doing business.
The article identifies the factors that most affected the deterioration of Ukraine's position in international ratings. Among the factors that have had the greatest impact on the deterioration of Ukraine's position in international ratings, corruption, political instability, inflation, ineffectiveness of the state policy towards investor protection and international investment attraction programs should be considered. The article analyzes the peculiarities of distribution of investments of leading branches of the national economy and their impact on the volume of sales at sectoral level. The main problems of attraction of investments for sustainable development of branches of national economy of Ukraine are revealed. In the course of the study, it was found that the same investments that were able to direct the real sector of the economy play a significant role in the development of economic processes of the main sectors of the economy. The main factors of internal and external character, which determine the sustainable development in the country are highlighted.
It is proposed to take into account and implement all possible measures for attraction of investments for the further sustainable development of the national economy of Ukraine. Стаття присвячена аналізу стану і специфіки розвитку провідних галузей національної економіки України. Досліджено зміни позиції України у світі за основними показниками міжнародних рейтингів, а саме: індексу інвестиційної привабливості, індексу глобальної конкурентоспроможності, індексу економічної свободи, індексу рівня легкості ведення бізнесу. В статті встановлено, які чинники найбільшою мірою вплинули на погіршення позицій України у міжнародних рейтингах. До чинників, які найбільшою мірою вплинули на погіршення позицій України у міжнародних рейтингах, треба віднести корупцію, політичну нестабільність, інфляцію, неефективність державної політики щодо захищення інтересів інвесторів та програм залучення міжнародних інвестицій. У статті проаналізовано у динаміці особливості розподілу інвестицій провідних галузей національної економіки та їх вплив на обсяги реалізації продукції на галузевому рівні. Виявлено основні проблеми залучення інвестицій для сталого розвитку галузей національної економіки України. В процесі дослідження було встановлено, що ті ж інвестиції, які вдалося спрямувати у реальний сектор економіки, відіграють значну роль у розвитку економічних процесів основних галузей економіки країни. Виділено основні чинники внутрішнього і зовнішнього характеру, які обумовлюють сталий розвиток в країні. Запропоновано враховувати та впроваджувати усі можливі заходи для залучення інвестицій для подальшого сталого розвитку національної економіки України. Статья посвящена анализу состояния и специфики развития ведущих отраслей национальной экономики Украины. Исследованы изменения позиции Украины в мире по основным показателям международных рейтингов, а именно: индекса инвестиционной привлекательности, индекса глобальной конкурентоспособности, индекса экономической свободы, индекса уровня легкости ведения бизнеса. В статье установлено, какие факторы в наибольшей степени повлияли на ухудшение позиций Украины в международных рейтингах. К факторам, которые в наибольшей степени повлияли на ухудшение позиций Украины в международных рейтингах, надо отнести коррупцию, политическую нестабильность, инфляцию, неэффективность государственной политики по защите интересов инвесторов и программ привлечения международных инвестиций. В статье проанализированы в динамике особенности распределения инвестиций ведущих отраслей национальной экономики и их влияние на объемы реализации продукции на отраслевом уровне. Выявлены основные проблемы привлечения инвестиций для устойчивого развития отраслей национальной экономики Украины. В ходе исследования было установлено, что те же инвестиции, которые удалось направить в реальный сектор экономики, играют значительную роль в развитии экономических процессов основных отраслей экономики страны. Выделены основные факторы внутреннего и внешнего характера, которые обусловливают устойчивое развитие в стране. Предложено учитывать и внедрять все возможные меры для привлечения инвестиций для дальнейшего устойчивого развития национальной экономики Украины.